Extraction and characterization of natural fibers from Pulicaria gnaphalodes plant and effect of alkali treatment on their physicochemical and antioxidant properties - Alsafran, Mohammed; Sadasivuni, Kishor Kumar; Haneesh, Julna Mohammed; Kasote, Deepak M. (Frontiers in Chemistry, 2024)
The study aimed to extract and characterize natural fibers from Pulicaria gnaphalodes (Vent.) Boiss. plants and assess the impact of alkali treatment on the physicochemical and antioxidant properties of these fibers. Fibers were extracted from dried P. gnaphalodes aerial parts by grinding with an average yield of 18.1%. Physicochemical and FTIR analysis revealed that the hemicellulose was mostly lost during alkali treatment. Results of the X-ray diffraction and thermogravimetric analysis indicated that the crystallinity and thermal stability of P. gnaphalodes fibers were considerably increased after alkali treatment. In antioxidant activity assessment studies, raw fibers of P. gnaphalodes showed significantly higher radical scavenging and reducing power potentials compared to the alkali-treated samples, indicating that the majority of antioxidant components such as lignin and other polyphenols were lost from P. gnaphalodes fibers during alkali treatment. In conclusion, the promising antioxidant activity of raw P. gnaphalodes can be utilized in developing functional materials, particularly for cosmetic and wound healing applications.